Bamboo Fibre as a Green Roof Material Layer to Improve Stormwater Quantity - MOHD ZAIDI BIN ALI, NURUL NATASHA; MOHD ARISH @ ARSHAD, NUR AINI (Progress in Engineering Application and Technology, 2025)
Rapid urbanization in Malaysia has increased stormwater runoff and urban floods, requiring long-term management solutions. While green roof systes have gained widespread adoption in advanced countries, their implementation in Malaysia faces perceptual and practical barriers, limiting the application of research findings. Green roofs present substantial benefits, including mitigating urban heat island effect, improving stormwater management and reducing pollution. This study investigates the use of bamboo fibre as a green roof material layer to enhance stormwater quality control. The innovation uses bamboo fibre, which are strong, absorb moisture, and are eco-friendly, along with recycled PET bottles to reduce plastic waste and improve green roofs. Two green roof models were constructed: a conventional model and an enhanced model utilizing bamboo fibers and PET bottles as a drainage layer based on the fibre bundle concept and filter layer using a concept non-woven bamboo fibre. Rainfall intensities were categorized as low (10 mm/h), moderate (34-47 mm/h), and high (>67 mm/h). A rainfall simulator was employed to evaluate the models hydrological performance, focusing on runoff retention rate, peak flow reduction and runoff coefficient. Experimental results revealed that the bamboo fibre-enhanced green roof outperformed the conventional model, achieving a stormwater retention rate up to 61% under high rainfall intensities. These findings highlight the effectiveness of integrating bamboo fibre and recycled PET materials in optimizing green roof systems. This study demonstrates the potiental of bamboo fibre as an innovative and renewable material for stormwater management, promoting sustainable urban development and advancing eco-friendly construction practices.